Effects of environrnental conditions on the radon daughters spatial distribution - Godoy, M.; Hadler, J. C.; Iunes, P. J.; Mestanza, S. N.; Oliveira, R. A.; Osorio, A. M.; Paulo, SR (Elsevier B.V., 2002)
The influence of environmental conditions on the indoor radon daughters spatial distribution is studied both theoretically and experimentally. Simple theoretical calculations indicate that ventilation and variation in the size distribution of aerosols should play an important role influencing the spatial distribution of indoor radon decay products, but experimental results indicate that these environmental factors have little influence on the spatial distribution of radon daughters near the walls of indoor environments. We have observed that the maximum effective range of the plate-out effect varies only between I and 3 cm in typical dwellings. (C) 2002 Elsevier B.V. Ltd. All rights reserved.
Keywords: radon daughters; indoor radon monitoring; CR-39; plate-out effect